Behavioural outcomes of parents and their children participating in the incredible years parenting programme in government hospitals in the Klang Valley, Malaysia - Masiran, Ruziana (2022)
Background: Children's emotional and behavioural problems (EBP) are associated with numerous negative psychosocial implications. Structured parenting programmes train parents to master good parenting skills to help children improve EBP. Controlled research demonstrated the effectiveness of the Incredible Years parenting programme (IYPP) as one such program. However, there is limited data concerning its use for school-going children, in clinical settings, and in developing Asian countries with collectivistic values like Malaysia. Objectives: The present study aimed to evaluate the effectiveness of the IYPP in decreasing EBP and parenting stress, improving parental mental health, and increasing parenting self-efficacy. Methodology: This randomised controlled study involved baseline and postintervention assessments at 2 weeks and 3 months, and was conducted in Kajang, Kuala Lumpur, and Selayang Hospitals. Mothers of 70 children aged 6- 12 years recruited through the paediatric clinics and the child and adolescent psychiatric clinics were randomly assigned to the IYPP (School Age Basic version) or a waitlist control group. Mothers rated EBP severity, parenting stress, parental mental health, and parenting self-efficacy using self-administered questionnaires. The weekly parenting programme ran for 14 weeks. Several modifications were made to the programme to accommodate the public health control measures during the COVID-19 pandemic period. Results: The intervention was effective in reducing EBP at 2 weeks postintervention and 3 months follow-up, B = -4.20, 95% CI [-6.68, -1.72], p = .001; B = -3.51, 95% CI [-6.37, -0.66], p = .016, respectively, particularly in respect to the externalising behaviours, B = -1.80, 95% CI [-3.09, -0.51], p = .006; B = - 1.89, 95% CI [-3.28, -0.50], p = .008, respectively. Concerning parental outcomes, the intervention was effective in reducing parenting stress at 3 months follow-up, B = -5.03, 95% CI [-9.16, -0.90], p = .017, and parent’s general stress at 2 weeks post-intervention, B = -4.06, 95% CI [-7.20, -0.92], p = .011. It was also effective in increasing parenting-self-efficacy at 2 weeks postintervention and 3 months follow-up, B = 34.11, 95% CI [11.32, 11.93], p = .003; B = 40.97, 95% CI [1 2.08, 17.29], p = .001, respectively. The effects on children’s EBP and parenting self-efficacy were sustained up to 3 months postintervention. However, the intervention had no significant effect in reducing parental anxiety or depression at 2 weeks post-intervention or 3 months followup, B = -2.91, 95% CI [-5.98, 0.15], p = .063; B = -2.17, 95% CI [-4.84, 0.50], p = .111, respectively; B = -2. 71, 95% CI [-5.42, 1.08], p = .190; B = -2.29, 95% CI [-5.16, 0.59], p = .119, respectively. Conclusion: The modified Incredible Years School Age Basic parenting programme is an effective tool in improving the emotions and behaviours of Malaysian school-going children as well as the parenting and mental health of their mothers. Evidence suggests that an established foreign parenting intervention can be transferred to the local population despite minimum resources, barriers to parental involvement, and various restrictions during a world health crisis.